Habitat associations of shovelnose sturgeon Scaphirhynchus platorynchus (Rafinesque, 1820) in the lower Platte River, Nebraska. (5th October 2017) - Hammen, J. J.; Hamel, M. J.; Rugg, M. L.; Pegg, M. A.
Summary: Human induced alterations of river systems are ubiquitous throughout the world. Alterations have reduced riverine habitat and negatively affected riverine species; therefore, it is crucial to understand what habitats are important to riverine fish at multiple scales. Most research has focused around microhabitats (i.e., depth) with little effort on how the reach scale habitat (i.e., geomorphic landscape) influences riverine fish abundance. We examined habitat associations of shovelnose sturgeon sampled with two gears (trotlines and trammel nets) at multiple spatial scales in the lower Platte River, NE, a system that has not been overtly altered in physical description. At a microhabitat scale, shovelnose sturgeon abundance was influenced by velocities and temperatures within the lower Platte River. The influence of velocity was contradictory between gears suggesting that gear limitations may have been present. Shovelnose sturgeon abundance increased in close proximity to a tributary interaction with the lower Platte River in both gears. Portions of the river with a relatively medium valley width, low‐medium sinuosity, and wide channel had the lowest shovelnose sturgeon abundance for both gears. Our results provide insight at multiple habitat scales on the landscape that may help managers and policy makers develop sound approaches to protecting and mitigating habitat for shovelnose sturgeon and other riverine species.